Planejamento da expansão de sistema de distribuição considerando redução de cenários de demanda e geração distribuída - Santos, Nicholas Eduardo Lopes dos (2018)
Traditionally, the maximum demand forecast in the planning horizon is used to determine the additions and reinforcements required for the expansion of a distribution system. The alternatives obtained with this model are considered overestimated because it considers a constant demand behavior along the planning horizon. Therefore, the search for a better representation of the demand in the planning models has been carried out, among them, the scenarios reduction based on clustering. This paper presents an analysis about the possibility of obtaining alternatives of expansion of lower cost in the planning of a distribution system representing the demand to be met and the distributed generation that can not be dispatched by more than one level. It is based on a planning model that considers a better representation of the load and generation that is solved through classical optimization techniques. The scenario reduction, used in the model, is based on levels groups that are defined and obtained whith k-means algorithm application. In addition to presenting expansion alternatives for different levels groups, it also shows that the processing times resulting from the combinatorial problem are acceptable.